Explaining and forecasting the US federal funds rate: a monetary policy model for the US - Clements, Matthew (Basingstroke, Hampshire ; New York : Palgrave Macmillan, 2004)
This book is a practical guide for the financial markets to explain United States Federal Reserve monetary policy and to make forecasts of the future federal funds rate.
Includes bibliographical references (p. 135-137) and
index.
&#x000A
osa 25/07/13
Loans
Keywords: Monetary policy -- United States; Interest rates -- United States; Federal funds market (United States)